Optimal Cut-Off Values of the Positive Lymph Node Ratio and the Number of Removed Nodes for Patients Receiving Resection of Bronchopulmonary Carcinoids: A Propensity Score-Weighted Analysis of the SEER Database - Chen, Qichen; Li, Mingxia; Wang, Pan; Chen, Jinghua; Zhao, Hong; Zhao, Jun (Frontiers in Oncology, 2021)
Background Although lymph node dissection (LND) has been commonly used for patients with bronchopulmonary carcinoids (PCs), the prognostic values of the positive lymph node ratio (PLNR) and the number of removed nodes (NRN) remain unclear. Methods Patients with resected PCs were identified in the Surveillance, Epidemiology, and End Results (SEER) database (2010–2015). The optimal cut-off values of the PLNR and NRN were determined by X-tile. The inverse probability of treatment weighting (IPTW) method was used to reduce the selection bias. IPTW-adjusted Kaplan-Meier curves and Cox proportional hazards models were used to compare the overall survival (OS) and cancer-specific survival (CSS) of patients in different PLNR and NRN groups. Results The study included 1622 patients. The optimal cut-off values of the PLNR and NRN for survival were 13% and 13, respectively. In both Kaplan-Meier analysis and univariable Cox proportional hazards regression analysis before IPTW, a PLNR ≥13% was significantly associated with worse OS (HR = 3.364, P<0.001) and worse CSS (HR = 7.874, P<0.001). These findings were corroborated by the IPTW-adjusted Cox analysis OS (HR = 2.358, P = 0.0275) and CSS (HR = 8.190, P<0.001) results. An NRN ≥13 was not significantly associated with worse OS in either the Kaplan-Meier or Cox analysis before or after IPTW adjustment. In the Cox proportional hazards analysis before and after IPTW adjustment, an NRN ≥13 was significantly associated with worse CSS (non-IPTW: HR = 2.216, P=0.013; IPTW-adjusted: HR = 2.162, P=0.024). Conclusion A PLNR ≥13% could predict worse OS and CSS in patients with PCs and might be an important complement to the present PC staging system. Extensive LND with an NRN ≥13 might have no therapeutic value for OS and may even have an adverse influence on CSS. Its application should be considered on an individual basis.